1982
DOI: 10.1126/science.7071589
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus-Like Syndrome in Monkeys Fed Alfalfa Sprouts: Role of a Nonprotein Amino Acid

Abstract: Hematologic and serologic abnormalities similar to those observed in human systemic lupus erythematosus (SLE) developed in cynomolgus macaques fed alfalfa sprouts. L-Canavanine sulfate, a constituent of alfalfa sprouts, was incorporated into the diet and reactivated the syndrome in monkeys in which an SLE-like syndrome had previously been induced by the ingestion of alfalfa seeds or sprouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(42 citation statements)
references
References 19 publications
0
41
0
1
Order By: Relevance
“…A small number of tentative, but nevertheless provocative, observations suggest relationships between foods and rheumatic diseases. These include associations of palindromic rheumatism with sodium nitrate hypersensitivity (20), black walnut ingestion with BehGet's syndrome (2 l), canavanine in alfalfa with systemic lupus erythematosus (22), fasting with an antirheumatic effect (5,8,9), chemical or food challenges (particularly wheat, corn, and beef) with symptomatic arthritis (3, RA with dairy products (23), food and tartrazine sensitivity with RA (24,25), systemic lupus erythematosus with environmental exposure to hydrazine (26), and rheumatoid-like synovitis in rabbits with consumption of cow's milk (27). We found that a particular prescribed diet (4) was of no demonstrable benefit compared with a placebo diet for RA.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of tentative, but nevertheless provocative, observations suggest relationships between foods and rheumatic diseases. These include associations of palindromic rheumatism with sodium nitrate hypersensitivity (20), black walnut ingestion with BehGet's syndrome (2 l), canavanine in alfalfa with systemic lupus erythematosus (22), fasting with an antirheumatic effect (5,8,9), chemical or food challenges (particularly wheat, corn, and beef) with symptomatic arthritis (3, RA with dairy products (23), food and tartrazine sensitivity with RA (24,25), systemic lupus erythematosus with environmental exposure to hydrazine (26), and rheumatoid-like synovitis in rabbits with consumption of cow's milk (27). We found that a particular prescribed diet (4) was of no demonstrable benefit compared with a placebo diet for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Both M. sativa seed and herb have been reported to induce a systemic lupus erythematosus (SLE)-like syndrome in female monkeys (Barnes et al 2007;Boon & Smith, 2004;Brinker, 2001;Malinow et al, 1982aMalinow et al, , 1982b. This activity has been attributed to canavanine, a nonprotein amino acid constituent, which has been found to have effects on human immunoregulatory cells in vitro (Jorge et al, 1985).…”
Section: Toxicity/side-effectsmentioning
confidence: 99%
“…Hydrazine, an organic solvent, similar to hydralazine, which is an antihypertensive associated with lupus, can cause a lupuslike syndrome from occupational exposure via inhalation (8). Other environmental chemicals, for example, an amino acid analogue found in alfalfa sprouts (9), can induce lupus. If a person develops an autoimmune disease, the first question he or she is ask- ed by a clinician is if they are taking any medications, and if so, these are discontinued as the possible cause of the autoimmune process with in many cases a curative outcome.…”
Section: Clinical Research Priorities: Vocs In Human Healthmentioning
confidence: 99%